Diagnostic migration between Specific Language Impairment and Autism Spectrum Disorder:: An exploratory study on the impact on Early Intervention Centres - Vacas Ruiz, Julia; Antolí Cabrera, Adoración; Sánchez-Raya, Araceli; Pérez-Dueñas, Carolina; Cuadrado Hidalgo, Fátima (Revista de Investigación en Logopedia, 2021)
Specific language impairment (SLI) and autism spectrum disorder (ASD) are very similar neurodevelopmental disorders mainly at early ages, which hampers early differential diagnosis. Diagnostic migration involves the shift of diagnosis either because of the development of the disorder or because of changes in diagnostic criteria or assessment tools. The aim of this study was to analyse the incidence and impact of this phenomenon in the centres of early intervention (CEIs) in Córdoba. Through an online survey available from March to May 2020, the CEIs managers provided quantitative data on the phenomenon as well as their appraisal of its impact on the intervention, prognosis, and family of children from 0 to 6 years. Ten public CEIs filled the survey. Results yielded a high incidence of diagnostic migration, this phenomenon occurred mainly from ASD to SLI. A significant disproportion of ASD and SLI diagnoses was also highlighted, being ASD the major one. The impact of diagnostic migration on child prognosis and family was deemed positive as it occurred mainly from a severe disorder to a more moderate one. Results from this study provide an initial approach to a relevant and unknown phenomenon. This line of research by increasing the sample deepening on socio-demographic information and including families perspective may improve our knowledge of SLI and ASD, as well as support clinical practice in early intervention.
Keywords: Specific Language Impairment; Developmental Language Disorder; Autism Spectrum Disorder; diagnostic migration; early childhood intervention